SYSTEM-WIDE ROUTING BASED MECHANISMS FOR ALLOCATING SERVICE QUALITY - kumar, Akhilesh (International Journal of Multidisciplinary Research and Studies, 2020)
Especially because of the growing use of mobile computing devices, the exchange of data has evolved into an essential element of our daily lives and was crucial to the operation of many computer programmers. To enable the communication features built into these apps, the underlying computer networks must meet a wide range of requirements. The latency or completion time of data transfer can be used to measure these needs, which are also referred to as Quality of Service (QoS) requirements. To maintain the appearance of a real-time connection, teleconferencing systems, for example, require that audio and visual data be provided with as minimal packet delay as feasible. Videos must be streamed over a large quantity of bandwidth in order for there to be little to no buffering while they are being viewed. In the absence of this, the playback of the video will be interrupted at the receiving end.